Tathma’in Al-Qulub dalam Perspektif Al-Qur’an - Mauliana Mauliana (TAFSE: Journal of Qur'anic Studies, 2018)
Various discussions are contained in the Qur'an, one of which is about the heart which is discussed in various aspects, including tathma`in al-qulub. Tathma`in al-qulub is a feeling of calm or a state of calm that is felt or comes from within the heart or heart. However, the understanding of peace of mind possessed by modern humans who are hedonists interprets it as stable or constant in the state of worldly (material) life or increasing dignity in the world. So the author wants to examine the views of the Qur'an about tathma`in al-qulub by looking at the context of the verses as well as the indicators and wisdom in the Qur'an. The method used in this study is the maudhu'i (thematic) method with a Sufism approach. This is done by collecting library data and using descriptive analysis techniques on the library materials. Based on the results of the study, the authors classify the verses of the Qur'an that talk about tathma`in al-qulub in four contexts of discussion, namely faith, aid in war, concealment of faith, and the commandment of remembrance. In addition, there are five basic indicators as a benchmark for tathma`in al-qulub namely repentance, faith and good deeds, piety, tawakkal, and patience. All of these things indicate the faith of a believer who believes and always maintains faith and continues to increase his faith so that he is able to achieve tathma`in al-qulub. Beragam pembahasan terdapat dalam al-Qur’an, salah satunya tentang qalbu yang dibahas dalam berbagai aspek, di antaranya tathma`in al-qulub. Tathma`in al-qulub adalah suatu perasaan tenang atau keadaan tenang yang dirasakan atau berasal dari dalam hati atau qalbu. Namun, pemahaman tentang ketenangan hati yang dimiliki oleh manusia masa modern yang hedonis memaknainya dengan stabil atau tetapnya keadaan kehidupan duniawi (materi) atau meningkatnya martabat di dunia. Sehingga penulis ingin mengkaji pandangan al-Qur’an tentang tathma`in al-qulub dengan melihat konteks ayat-ayat serta indikator dan hikmahnya dalam al-Qur’an. Metode yang digunakan pada kajian ini adalah metode maudhu‘i (tematik) dengan pendekatan tasawuf. Dilakukan dengan mengumpulkan data kepustakaan dan menggunakan teknik analisis deskriptif terhadap material perpustakaan tersebut. Berdasarkan hasil  penelitian, penulis mengelompokkan ayat-ayat al-Qur’an yang berbicara tentang tathma`in al-qulub dalam empat konteks pembahasan, yaitu keimanan, bantuan dalam peperangan, penyembunyian keimanan, dan perintah zikir. Selain itu, terdapat lima indikator dasar sebagai tolak ukur tathma`in al-qulub yakni taubat, beriman dan beramal saleh, takwa, tawakkal, dan sabar. Semua hal tersebut mengindikasikan keimanan seorang mukmin yang beriman dan senantiasa menjaga keimanan serta terus meningkatkan keimanannya sehingga mampu mencapai tathma`in al-qulub.